663 OCCURRENCE OF VENTRICULAR AND SUPRAVENTRICULAR ARRHYTHMIAS IN BRUGADA SYNDROME: RESULTS OF A TERTIARY REFERRAL CENTER EXPERIENCE. (15th December 2022) - Menè, Roberto; Dagradi, Federica; Giovenzana, Fulvio; Brasca, Francesco Maria; Girardengo, Giulia; Parati, Gianfranco; Perego, Giovanni Battista; Crotti, Lia; Schwartz, Peter J
Abstract: Brugada Syndrome (BrS) is one of the most common channelopathies and is related to an increased risk of ventricular arrhythmias. Current guidelines recommend the implantation of a Cardiac Defibrillator (ICD) in those patients that have a diagnostic ECG pattern and a history of aborted cardiac arrest. Nevertheless, management of asymptomatic patients, who are the majority, remains controversial as their risk stratification is often based on the results of an inductive Electrophysiologic Study (EPS) the predictive accuracy of which is debated. Furthermore, BrS has also been associated to an increased risk of supraventricular tachy- and bradyarrhythmias. Aim: to describe the occurrence of ventricular and supraventricular arrhythmias in BrS patients that receive an implantable cardiac monitoring device following an EPS study Methods: we retrospectively identified all BrS patients followed at our tertiary referral centre that were candidate to an EPS. Patient were candidate to EPS if: (1) they had a spontaneous diagnostic Brugada pattern at ECG and (2) they had no history of previous ventricular arrhythmias or high-risk syncope. Those patients that tested positive for induction of a sustained ventricular arrhythmia at EPS received an ICD; those that tested negative received an ILR. During the follow-up visits, implantable devices were interrogated for the occurrence of ventricular and supraventricular arrhythmias. Results: We identified 87 patients matching the inclusion criteria. Of these, 31 (35.7%) received an ICD for a positive EPS while the remaining 56 (64.3%) received an ILR. Over a mean follow-up period of 34 months (IQR 5-45, 249 patient-year), only one patient in the EPS positive group experienced a ventricular arrhythmia effectively treated by the ICD (0.3 events per patient-year) compared to zero patients in the EPS negative group (100% NPV, 3.2% PPV). Notably, implanted devices allowed for the detection of supraventricular arrhythmias in 12 out of the 87 patients (14%): 5 were cases of symptomatic sinus bradycardia, with an indication to permanent pacing in two of them, and 7 were cases of atrial tachycardia/fibrillation. Discussion: in our registry, consistently with previous literature, ventricular arrhythmias in BrS patients are rare and a negative EPS identifies with high accuracy those that are at low risk for this event. Conversely, a positive EPS may overestimate the risk of these patients resulting, according to current practice, in frequent implantations of ICD that will never be required for defibrillation. Although the patient-year observation period of the presented cohort is sizeable, our results should be furtherly validated on multi-center cohorts with even longer follow-up periods. Nonetheless, our results support the idea that risk stratification tools other than EPS are probably needed to properly identify the minority of BrS patients that will experience a ventricular arrhythmia throughout their life. In addition, we report a considerable number of supraventricular arrhythmias recorded by the implanted cardiac monitoring devices in our population. This is consistent with the knowledge of BrS patients being at increased risk of sinoatrial node dysfunction and atrial fibrillation and may elicit a more widespread and methodical screening for these events.